COVID-19: War protocol to fight the pandemic - Rossani Alatrista, German (2020)
During the medical training years, in one way or another, we have obtained knowledge and have prepared in the best possible way for emergencies and/or natural disasters. In the last 25 years, action protocols have been executed and implemented in a successful manner before endemics, epidemics and pandemics, such as Influenza, Ebola and SARS.What we have been observing in the last 3 months makes us reflect on the reactions before this global emergency and the ethical problems that have emerged due to COVID-19. We are moved and it sparks diverse reactions that to look beyond the initial emotions and generosity.